Adaptive Changes in the Dynamics of Visual Attention With Extended Practice - Junker, Matthew S.; Park, Bo Youn; Shin, Jacqueline C.; Cho, Yang Seok (Frontiers in Psychology, 2020)
Previous research indicates that visual attention can adapt to temporal stimulus patterns utilizing the rapid serial visual presentation (RSVP) task. However, how the temporal dynamics of an attentional pulse adapt to temporal patterns has not been explored. We addressed this question by conducting an attentional component analysis on RSVP performance and described changes in attentional dynamics that were accompanied by explicit learning about predictable target timing. We utilized an RSVP task in which a target letter appeared either in two possible RSVP positions in fixed-timing conditions or in random positions over 1, 2, or 3 days of training. In a transfer phase, the target appeared in previously presented or new positions. Over three days of practice the target identification rate and the amplitude of a putative attentional pulse increased while its variability decreased. These changes reflected general learning in the RSVP task resulting in attentional dynamics more efficiently focused on the target. Interestingly, target identification rates and the measure of attentional efficacy or amplitude of an attentional pulse were associated with explicit learning. The current study is the first to provide a detailed description of practice related adaptation of attentional dynamics and suggests that timing specific changes might be mediated by explicit temporal learning.